2013
DOI: 10.1186/1471-2482-13-40
|View full text |Cite
|
Sign up to set email alerts
|

Bohler’s angle’s role in assessing the injury severity and functional outcome of internal fixation for displaced intra-articular calcaneal fractures: a retrospective study

Abstract: BackgroundControversy exits over the role of Böhler’s angle in assessing the injury severity of displaced intra-articular calcaneal fractures and predicting the functional outcome following internal fixation. This study aims to investigate whether a correlation exists between Böhler’s angle and the injury severity of displaced calcaneal fractures, and between surgical improvement of Böhler’s angle and functional outcome.MethodsPatients treated operatively for unilateral closed displaced intra-articular calcane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 32 publications
2
59
1
5
Order By: Relevance
“…Opinions vary as to which one of these features is of key importance in the treatment. Makki, Su, and Isaacs conducted three independent studies and found that it is the postoperative Böhler's angle that allows for pre dicting a good functional result [36][37][38]. The analysis of our study results has led us to similar conclusions.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Opinions vary as to which one of these features is of key importance in the treatment. Makki, Su, and Isaacs conducted three independent studies and found that it is the postoperative Böhler's angle that allows for pre dicting a good functional result [36][37][38]. The analysis of our study results has led us to similar conclusions.…”
Section: Discussionsupporting
confidence: 74%
“…Zda nia są po dzielo ne. Mak ki, Su oraz Isa acs, w trzech nie za le żnych ba da niach, do szli do wnio sku, że to po ope ra cyj na war tość ką ta Böhle ra pro gno zu je do bry wy nik funkcjo nal ny [36][37][38]. Ana li zu jąc wy ni ki ba da nej gru py treated with open reduction and internal fixation with a plate and screws, we achieved 16 excellent (35.5%) and 10 good (22.6%) results.…”
Section: Discussionunclassified
“…In addition, a negative Böhler's angle, a negative calcaneal compression angle, or a fracture into the anterior surface of the calcaneus is associated with worse patient outcomes. The literature reports contrasting results in the predictive value of the Böhler's angle [11][12][13]36]. The studies from Loucks et al (1999) and Persson et al (2015) demonstrated that a negative Böhler's angle in patients with an intra-articular calcaneal fracture is negatively related to health-related quality of life outcome [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…However, the subtalar joint frequently collapses (calcaneal collapse) post-operatively to some extent, which can be seen at radiological follow-up [11,14,24]. Several authors noted a correlation between initial BA and outcome [3,10,15,18,22,24]. The BA at time of admission appears to be a valuable prognosticator for functional longterm results [18].…”
Section: Introductionmentioning
confidence: 99%